2017
DOI: 10.3892/ijo.2017.4202
|View full text |Cite
|
Sign up to set email alerts
|

The biology and function of extracellular vesicles in nasopharyngeal carcinoma (Review)

Abstract: Extracellular vesicles are a heterogeneous group of membrane-enclosed vesicles, which play an important role in intercellular communication. Increasing number of studies have shown that tumor-derived extracellular vesicles might be involved in the transfer of oncogenic cargo (proteins, lipids, messenger RNA, microRNA, non-coding RNAs and DNA) through which cancer cells could shape the tumor microenvironment and influence tumor progression. Nasopharyngeal carcinoma-derived extracellular vesicles have also repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 118 publications
1
10
0
Order By: Relevance
“…The same results were achieved in in vitro studies with exosomes derived from metastatic tumor cells [100]. Moreover, EVs from nasopharyngeal carcinoma (NPC) cells are enriched with HCLS1-associated protein X-1 (HAX-1) and could accelerate the proliferation and migration of HUVECs [134].…”
Section: Molecular Cargo Of Tex Influencing Angiogenesis / Tex Conversupporting
confidence: 64%
See 1 more Smart Citation
“…The same results were achieved in in vitro studies with exosomes derived from metastatic tumor cells [100]. Moreover, EVs from nasopharyngeal carcinoma (NPC) cells are enriched with HCLS1-associated protein X-1 (HAX-1) and could accelerate the proliferation and migration of HUVECs [134].…”
Section: Molecular Cargo Of Tex Influencing Angiogenesis / Tex Conversupporting
confidence: 64%
“…In a variety of cancer types, EVs have been shown to increase tube formation, migration, cell-cell adhesion and proliferation in ECs [100,102,113,[127][128][129][130][131][132][133]. Studies have been performed to determine the relationship between EVs and pathological angiogenesis [134]. It was demonstrated that HUVECs induce pathological angiogenesis [135] via an abundance of genetic information transferred by EVs [136].…”
Section: Molecular Cargo Of Tex Influencing Angiogenesis / Tex Convermentioning
confidence: 99%
“…The crucial role of EVs in a wide variety of malignancies highlights their potential functions as biomarkers and therapeutic targets. 19 , 20 Hence, the current study set out to investigate the functional interaction of NPC-cell-derived EV-shuttled miR-144 with FBXW7 in relation to NPC tumorigenesis and angiogenesis. Collectively, the experimental data provided evidence suggesting that miR-144 carried by EVs derived from NPC cells contributed to angiogenesis of HUVECs via the upregulation of HIF-1α and VEGF-A through target inhibition of FBXW7, which has the potential to be applied in the development of therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Prior evidence has reported that RUNX2 can promote the occurrence of vascular injury repair (4), while RUNX2 can activate the expression of miR-23a (5). Recently, more studies shed light on the potential of miR-23a acting as biomarkers and therapeutic targets (20,21). Emerging evidence has highlighted that miR-23a can inhibit apoptosis and inflammation during vascular injury, thereby inhibiting vascular injury (10).…”
Section: Discussionmentioning
confidence: 99%